The Model of Marketing and Sales Outcomes in the Bitumen Market - Esfandiar , Masoud; Asayesh , Farzad; Rousta, Alireza; Hashemi , Seyed Mahmood (Management Strategies and Engineering Sciences, 2025)
Marketing and sales outcomes are typically shaped based on long-term and interactive relationships between companies. These markets often involve complex and specialized products and services that require technical knowledge and a deep understanding of customer needs. The marketing and sales process in these markets comprises multiple stages, including identifying customer needs, presenting customized proposals, conducting complex negotiations, and establishing long-term contracts. In this environment, intercompany relationships are highly significant, and decision-making is primarily carried out by purchasing teams composed of managers and various experts. The objective of this study was to present a model of marketing and sales outcomes in industrial markets. This study is applied in terms of its objective and qualitative in terms of methodology, employing a grounded theory approach. Data and information were collected through a literature review and semi-structured interviews. Based on purposive sampling, 14 managers and experts from companies operating in the bitumen industry were selected in 2024. The conducted interviews were coded using ATLAS.TI software. The results identified the marketing and sales outcomes model, including increased market share, enhanced customer satisfaction, improved profitability, market differentiation, and optimized marketing performance. The marketing and sales outcome model in the bitumen market necessitates specific approaches that differ significantly from other industries. In this industry, emphasis is placed on establishing long-term customer relationships, extensive networking, and maintaining strong connections with key customers. Therefore, companies must actively engage in forming strategic relationships with major customers, such as construction contractors and road construction companies, to leverage the long-term benefits of these relationships.